Pelatihan Jurnalistik untuk Menggali dan Meningkatkan Potensi Siswa dalam Membantu Pengembangan Wisata Daerah Pacitan - Kartinawati, Erwin; Purwasito, Andrik (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
This community service was to help the community utilize the internet as a means of promoting tourism or all the potential in the Pacitan area, East Java. The intended target was for students to be more productive in utilizing their time in this information and digital era. Research shows that students spend more time surfing cyberspace, fulfilling their entertainment needs than studying. Through journalism training, it was hoped that students who were still active members of society and had high curiosity could canalize it through positive activities. The way to do it was by making journalistic products that could be published in media. How to make journalistic products that could be suitable for publication in the media or were of interest to the public as a means of regional promotion was the goal of this activity. This activity was part of efforts to increase society's digital competence.